The spectable of pompousity in funerals: The 1816 Requiem of José Maurício Nunes Garcia (Per Musi, 2019)
George Balandier in his work "Le pouvoir sur scènes" (1980) states that forms of power are represented by the spectacularization of rituals, becoming a "theatocracy" or performance of a set of behaviors that produces an idealized image of themselves, for themselves and for others. In the Luso-Brazilian world and in Brazil during the two imperial periods, pompous funerals were routine, becoming an ephemeris that functioned both as a fitting send-off for the deceased, but also as a representation of their power. When constructing the spectacle of death, ephemeral visual arts and music stood out. In the latter, the Requiem Masses stood out. This article examines the 1816 Requiem by Father José Maurício Nunes Garcia, composed for the funeral of Queen Dona Maria I, progenitor of Dom João VI. The objective is to situate and problematize this work as the image of death realized through sound, and its place in the performance spaces in the Johannine times.